The Internal Political and Economic Structure of Old Babylonian Nippur: The Guennakkum and his "House" - Robertson, John F.
photos CBS 7625, 7580, 7506, 7111, 7110, UM 29-15-885, 29-15-879, 29-15-855, 29-15-870; ersch. 1985.